A Study of Selected Aḥādītḥ on Fashion in Ṣaḥihu Al-Bukhārī and Their Implications on The Contemporary Female Muslims - Suraju, Saheed Badmus; Kolawole, Ramota Damilola (Al-Basirah Journal, 2022)
Extreme self-beatification among female in the modern time has resulted into several cases of self-inflicted injuries. Despite the prohibition of Islām, on any form of practices that could lead to self-destruction or harm by Islām, some contemporary female Muslims are found of this attitudes even though adornments is not out rightly condemned in Islam but are regulated in different aḥādītḥ of the Prophet. This paper therefore attempts to aim at examining some aḥādītḥ on fashion as related to women under the book of dress in Ṣaḥīḥ-ʼl-Bukhārī as well as their adverse implications on the contemporary female Muslims. The study adopts descriptive, exegetical and phenomenological research methods. The findings reveal that there are dangers in applying artificial hairs, eyelashes, and body tattooing, and that some cosmetics and beauty salons, despite the danger and detriment of artificial beauty to their clients, are unwilling to give up lucrative business. This paper concludes that, there is a dire need to curb extreme artificial adornments, in order to drastically reduce the high level of indecency, obscenity, vulgarity and immorality among the female Muslims, old or young in the contemporary society. It therefore, recommends that fashion and beauty policy should be made in addition to the efforts in creating awareness on the dangers in extreme artificial adornments.